Changes in Isoflavone Profile from Soybean Seeds during Cheonggukjang Fermentation Based on High-Resolution UPLC-DAD-QToF/MS: New Succinylated and Phosphorylated Conjugates - Suji Lee; Ryeong Ha Kwon; Ju Hyung Kim; Hyemin Na; So-Jeong Lee; Yu-Mi Choi; Hyemyeong Yoon; So Young Kim; Yong-Suk Kim; Sang Hoon Lee; Seon Mi Yoo; Heon-Woong Kim; et al. (Molecules, 2022)
In this study, thirty-eight isoflavone derivatives were comprehensively identified and quantified from the raw, steamed and fermented seeds of four selected soybean cultivars based on UPLC-DAD-QToF/MS results with reference to the previously reported LC-MS library and flavonoid database, and summarized by acylated group including glucosides (Glu), malonyl-glucosides (Mal-Glu), acetyl-glucosides (Ac-Glu), succinyl-glucosides (Suc-Glu) and phosphorylated conjugates (Phos) in addition to aglycones. Among them, Suc-Glu and Phos derivatives were newly generated due to fermentation by B. subtilis AFY-2 (cheonggukjang). In particular, Phos were characterized for the first time in fermented soy products using Bacillus species. From a proposed roadmap on isoflavone-based biotransformation, predominant Mal-Glu (77.5–84.2%, raw) decreased rapidly by decarboxylation and deesterification into Ac-Glu and Glu (3.5–8.1% and 50.0–72.2%) during steaming, respectively. As fermentation continued, the increased Glu were mainly succinylated and phosphorylated as well as gradually hydrolyzed into their corresponding aglycones. Thus, Suc-Glu and Phos (17.3–22.4% and 1.5–5.4%, 36 h) determined depending on cultivar type and incubation time, and can be considered as important biomarkers generated during cheonggukjang fermentation. Additionally, the changes of isoflavone profile can be used as a fundamental report in applied microbial science as well as bioavailability research from fermented soy foods.